The Construction of Phosphorus-Doped g-C3N4/Rh-Doped SrTiO3 with Type-II Band Alignment for Efficient Photocatalytic Hydrogen Evolution - Bin Wang; Peng Li; Hanjing Hao; Huijie He; Hairui Cai; Fanfan Shang; Bei An; Xiaoqian Li; Shengchun Yang (Nanomaterials, 2022)
It is of great importance to promote charge separation in photocatalysts for enhanced photocatalytic activity under visible light irradiation. In this work, a type-II heterostructured photocatalyst was constructed by compositing phosphorus-doped g-C3N4 (P-CN) and Rh-doped SrTiO3 (Rh-STO) via a thermal calcination treatment. A series of characterizations were conducted to investigate the structure of heterostructured P-CN/Rh-STO. It was found that Rh-STO interacted with in situ generated P atoms from the decomposition of P-CN during the calcination process, thus leading to the formation of heterojunction of P-CN/Rh-STO. Compared with the single component, i.e., P-CN or Rh-STO, the obtained P-CN/Rh-STO showed superior photocatalytic activity to that of both P-CN and Rh-STO due to the effective charge separation across the heterojunction between P-CN and Rh-STO.